TAQNIN FIKIH : Transformation of Marriage Law in Indonesia - Fernanda, Ahmad; Salma, Salma; Hidayat, Rahmat (Universitas Islam Negeri Mataram, 2024)
Indonesia has a pluralist background, so realizing one rule accommodating all interests is a challenge. Among them is the unification of the rules on marriage. The purpose of this study is to explore historically the growth and development of taqnin from time to time, taqnin of marriage law in Indonesia, the legality of post-taqnin marriage law, challenges and opportunities, and challenges of taqnin. This literature research method uses quantitative with an exploratory analysis approach, namely analyzing fikih munakahat products transformed into positive law. Data processing by managing library materials (library research). Secondary data sources are Law Number 1 of 1974 concerning Marriage and the Compilation of Islamic Law (KHI) and books and articles based on OJS (Open Journal System). Techniques for analyzing the data obtained were exploratory and descriptive analysis using the techniques of reduction, display, and verification. The results showed that, based on historical aspects, taqnin had been pursued since the abasiyah daulah but has experienced ups and downs in its implementation. Second, The transformed legal product is dynamic. Third: Munakahat jurisprudence has gone through the process of taqnin to have the legality of state law, so it becomes the primary source in marriage issues. Fourth: The opportunities and challenges faced are internal and external.